Maternal exacerbating and protective factors that shape the prevalence and severity of child attention-deficit hyperactivity disorder: a narrative review - Thorsheim, Corinne; Khan, Sana; Lu, Ye; Kauffman, Robert P. (Frontiers in Psychiatry, 2025)
Attention deficit hyperactivity disorder (ADHD) is a widely prevalent neurodevelopmental disorder that affects millions of children and adolescents in the U.S. Despite the growing number of diagnoses, the maternal exacerbating and protective factors influencing ADHD symptom severity in offspring remain largely understudied. This narrative review examines the interplay between genetic and epigenetic factors, focusing on specific single nucleotide polymorphisms, polygenic risk scores for ADHD and comorbidities, mitochondrial DNA haplotypes, and X-linked inheritance. Key epigenetic influences include maternal gestational weight gain, young parental age, parental gene–psychopathology interactions, shared genetic loci between maternal educational attainment and ADHD, maternal prenatal stress, maternal hostility and maltreatment, postnatal household chaos, and parenting styles, all which shape ADHD symptom severity in the context of genetic predispositions. Importantly, the positive effects of elevated socioeconomic status and positive parenting on symptom severity may also be influenced by maternal genetic factors, representing an avenue for further research. The maternal environmental factors associated with ADHD in offspring, such as in utero acetaminophen exposure, maternal diet, vitamin D deficiency, and exposure to toxins, particularly from maternal smoking, are highlighted. Ultimately, this review seeks to uncover the combined impact of maternal environmental and existing factors on underlying parental genetics—a critical aspect often overlooked in existing studies. Clinical implications are also addressed, particularly concerning differences in beta and theta wave activity and variations in cerebral blood flow in the dorsolateral prefrontal cortex between children with ADHD and those with comorbid autism spectrum disorder (ASD). By understanding these multifaceted factors, especially maternal contributions, alongside emerging clinical diagnostic strategies, better targeted interventions can be aimed at enhancing treatment efficacy and improving long-term outcomes for children with ADHD.